Rigid Social Structure of the Nineteenth-Century England in Jane Austen’s Novel Pride And Prejudice - Balqis, Kesya Aprillia; Manugeren, M.; Anayati, Wan (Universitas Islam Sumatera Utara, 2026)
This study examines the rigid social structures of nineteenth-century England as depicted in Jane Austen's Pride and Prejudice. The research investigates how inflexible social hierarchies, characterized by distinct class stratifications—upper, middle, and lower classes—constrained individual agency, particularly among women. The analysis focuses on four pivotal dimensions: marriage as a social transaction, social hierarchy and etiquette, land and wealth ownership, and the manifestations of prejudice and discrimination. Despite extensive scholarship on Austen's social critique, limited attention has been paid to the interaction between class stratification and individual agency within the specific context of nineteenth-century English property relations. Employing a Marxist literary framework, this research elucidates how material conditions fundamentally shaped character motivations, interpersonal dynamics, and socioeconomic opportunities. Through a qualitative analysis of dialogue, narration, and descriptive elements within the novel, the findings demonstrate how stringent social norms limited individual autonomy and engendered pervasive conflict between personal desires and societal imperatives. This study contributes to existing scholarship by revealing how Austen's narrative simultaneously critiques systemic inequality while exposing the psychological constraints imposed on middle-class women within a patriarchal property system. Ultimately, this study highlights Austen's sophisticated critique of the systemic injustices inherent in the nineteenth-century British class system, while underscoring the enduring relevance of these themes within contemporary social contexts.